2008
DOI: 10.1093/ejechocard/jen254
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and reproducibility of left ventricular outflow tract diameter measurement using transthoracic when compared with transesophageal echocardiography in systole and diastole

Abstract: We present the data regarding accuracy and reproducibility of LVOTd measurements by TTE when compared with TEE. LVOTd measurements at end-diastole may be helpful when systolic images are suboptimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 20 publications
(42 reference statements)
0
39
0
Order By: Relevance
“…However, according to literature, variations of the annulus size during the cardiac cycle are limited [9,32], especially in patients with severe AS with severe calcifications of the aortic valve and the aortic wall and annulus. A previously published study establishing normative values for ascending aorta measurements found large inter-individual variations in diameters and distances but with limited intra-individual variations during the cardiac cycle [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to literature, variations of the annulus size during the cardiac cycle are limited [9,32], especially in patients with severe AS with severe calcifications of the aortic valve and the aortic wall and annulus. A previously published study establishing normative values for ascending aorta measurements found large inter-individual variations in diameters and distances but with limited intra-individual variations during the cardiac cycle [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CMR and DSCT as well as TEE measurements were not performed exactly at the same time (end-systole to mid diastole versus early-systole). However, variations of the annulus size during the cardiac cycle are limited [15,20]. In 5 patients atrial fibrillation was present.…”
Section: Discussionmentioning
confidence: 99%
“…Although CO can also be measured at other locations (mitral valve annulus [6], ascending aorta [7,8], the right ventricular outflow tract (RVOT) [9] and pulmonary artery [10]), this has been less validated. While cross section of the LVOT at diastole (LVOT d ) can also be measured [11], large inter-observer variability exists up to 0.2 cm [12]. There also exists a difference between LVOT measured by transthoracic (TTE) and transesophageal echocardiography (TEE).…”
Section: Assessment Of LV Systolic Function Cardiac Output (Co)mentioning
confidence: 99%
“…There also exists a difference between LVOT measured by transthoracic (TTE) and transesophageal echocardiography (TEE). It has been revealed that TTE tends to underestimate the LVOT by 0.1 cm [12]. Variation of LVOT in the general population ranges between 18 and 22 mm [13,14] and is related to body surface area.…”
Section: Assessment Of LV Systolic Function Cardiac Output (Co)mentioning
confidence: 99%